Fabrication of AgI/ZnO photocatalyst for mechanistic study and photodegradation of tetracycline - Muhamad Hissam, A. N.; Sinar Mashuri, S. I.; Chayed, N. F.; Rozali Annuar, N. H.; Asikin-Mijan, N.; Ibrahim, S. F.; Othman, N. H.; AbdulKareem-Alsultan, G.; Tan, Y. H.; Rashid, U.; Taufiq-Yap, Y. H.; Ibrahim, M. L. (Springer Nature, 2025)
Tetracycline is an antibiotic known to inhibit the growth of microorganisms in soil and water. Often, pharmaceutical companies release unwanted and expired antibiotics, leading to water pollution. This study involved the synthesis of AgI combined with ZnO to form heterostructures by a wet impregnation method to degrade tetracycline molecules. The primary objective is to explore the mechanistic pathways of tetracycline degradation under visible light irradiation. The combination of AgI and ZnO is chosen due to their enhanced photocatalytic properties when coupled, as ZnO provides a stable, wide-bandgap semiconductor, while AgI improves visible light absorption, extending the efficiency of the catalyst. Catalyst characterization by Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy analysis confirmed the presence of AgI and ZnO phases, while X-ray Diffraction showed distinct crystalline structures of both. Surface area analysis indicated a controlled pore volume of 31.78 nm and a high surface area of 27.29 m2/g for the AgI/ZnO composites. The Tauc plot demonstrated that AgI doping reduced the ZnO optical energy bandgap from 3.39 to 2.83 eV. The AgI/ZnO catalyst achieved up to 89.38% degradation of tetracycline at 10 mg/L concentration using 0.01 g of AgI/ZnO, under a 150-W metal halide lamp at pH 9 in 90 min. Scavenger tests identified superoxide radicals and electrons as the primary species facilitating tetracycline photodegradation. The AgI/ZnO photocatalysts showed remarkable reusability, maintaining efficiency over five cycles. Therefore, AgI/ZnO holds great potential as an effective photocatalyst for breaking down organic pollutants like tetracycline using visible light energy.